Effectives of Monetary Policy under the High and Low Economic Uncertainty States: Evidence from the Major Asian Economies - Mehmet Balcilar; Zeynel Abidin Ozdemir; Huseyin Ozdemir; Gurcan Aygun; Mark E. Wohar (Institute of Labor Economics (IZA), 2021)
This study examines the monetary policy effectiveness of five major Asian countries (China, Hong Kong, India, Japan, and South Korea) using a quantile vector autoregression (QVAR) model-based spillover estimation approach of Balcilar et al. (2020b) at different quantile paths. To do this, we first obtain the spillover index from interest rate to industrial production and consumer price index under the high and low levels of uncertainty. The full sample results from our analysis provide partial supporting evidence for the economic theory, which asserts that monetary policy efficiency must fall during periods of high economic uncertainty. Furthermore, this approach also allows us to uncover asymmetric effects of economic policy uncertainty and lending rate on macroeconomic indicators. The impacts of interest rate and domestic and foreign (US, EU) uncertainty shocks on major Asian markets present significant asymmetric characteristics. Moreover, our time-varying results suggest that monetary policy shocks are more effective and potent on Asian economies during very low and very high uncertain times than normal economic periods.
Keywords: C32; E44; F42; G01; 330; economic policy uncertainty; monetary policy efficiency; quantile spillover; QVAR